DO COMPANY CHARACTERISTICS INFLUENCE THE QUALITY OF INTEGRATED REPORTING? A STUDY OF SOUTH AFRICAN JSE TOP 100 LISTED COMPANIES. LISTED COMPANIES - Phaswana, Malilimalo (College of Accounting, 2019)
This dissertation investigates whether a statistically significant relationship exists between a company’s corporate characteristics and the quality of its integrated report. The JSE Top 100 companies are used as the study population, with the Ernst & Young Excellence in Reporting ratings used as the framework for assessing integrated reporting quality. A multiple multivariate regression analysis was employed to assess the impact of ten company characteristics that were found to be prominent by other studies. The results show that firm size, board diversity, board independence and firms in the resource sector show a statistically significant positive association with components of integrated reporting quality as described in the Integrated Reporting Framework. The results suggest that firms with stronger adherence to good corporate practices, with firm board diversity and board independence as a possible indicator, are more responsive to the need for quality integrated reporting. Further, firms with greater accountability to stakeholders through their size of sector also appear to respond to this obligation through increased disclosures.